Staffing agricultural information systems - Nair, R Raman (New Delhi Ess Ess, 2000)
Staffing agricultural information systems focuses on the manpower strategies required for exploting our agricultural knowledge resources if agricultural information systems are to give intended results,library and information science and electronics and c
Keywords: Information networks; Agriculture-Information services; Agricultural information network